(untitled) (Vietnam Journal of Community Medicine, 2024)
Objective: To describe the medical incidents that occurred at Bac Giang General Hospital in 2023. Method: A cross-sectional descriptive study utilizing secondary data analysis. Results: A total of 223 medical incident reports were recorded, with 96.9% being voluntary submissions. The Neurology Department reported the highest number of incidents; nurses, technicians, and midwives accounted for 68.6% of the reported incidents; the majority of incidents (53.8%) directly impacted patients but did not cause harm; medical equipment-related incidents constituted the largest category, representing 36.3% of the total. Conclusions: Medical staff need to take a proactive approach in reporting medical incident reports and adhere strictly to the hospital’s reporting regulations.